2010
DOI: 10.1111/igc.0b013e3181f0df98
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler Area in the Diagnosis of Endometrial Cancer

Abstract: The PDA is an effective measure in the diagnosis and exclusion of endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…The diagnostic efficiency of color intensity visual analog scale (VAS) scores, a vascular index or a Doppler score seems comparable. Concordant with our findings, there is less observer variation in the distinction of Doppler flow patterns in trained hands than in inexperienced hands.…”
Section: Discussionsupporting
confidence: 87%
“…The diagnostic efficiency of color intensity visual analog scale (VAS) scores, a vascular index or a Doppler score seems comparable. Concordant with our findings, there is less observer variation in the distinction of Doppler flow patterns in trained hands than in inexperienced hands.…”
Section: Discussionsupporting
confidence: 87%
“…The addition of power Doppler (PD) has further increased the sensitivity and specificity of TVUS to diagnose endometrial polyps . However, few studies have described how to distinguish complex endometrial lesions in infertility using color Doppler . Furthermore, the prevalence of different endometrial pathologies in cases of infertility has not been fully documented.…”
Section: Introductionmentioning
confidence: 99%
“…It is able to detect subtle changes in the endometrium and it has been observed that endometrial thickness <4 mm is usually associated with normal morphology (5). In patients with thickened endometrium, a secondary test such as power Doppler could play a role in refining the diagnosis (6). Doppler velocimetric study of the uterine artery offers a simple, noninvasive and valuable method in screening women with postmenopausal bleeding.…”
Section: Introductionmentioning
confidence: 99%